Menelisik Peran Pesantren dalam Regenerasi Ulama Perempuan - Fahrina Yustiasari Liriwati; Sudirman Anwar (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2022)
In the early days of modernity entered the muslim nations of the world, namely the 19th century and the beginning of the 20th century, where the work of female clerics was not seen and recognized. This condition affects the subconscious of the world's Muslims to date, so it takes extra work to bring about the existence of female clerics and recognize their presence and authority. Islam places women as the highest symbol of spirituality by placing women's spirituality as the path to the noblest place of heaven. The breeding of females was born in a societal situation that actually insulted women. Prophet SAW brought prophetic treatises by convincing that what distinguishes women and men before Allah Almighty is the quality of their selfhood, the quality of their faith. Therefore, the birth of superstitious educational institutions for female students from the beginning is concrete evidence of the pesantren's partiality towards the mainstreaming of women. It's just that this has not supported the birth of a qualified female scholar, because the level is new at the secondary education level and the main target is to be able to equip them with the basics of women's education as prospective educators for their families and children.